SYNOPSIS TO THE INDIAN GENERA OF THE FISHES OF THE FAMILY SCIAENIDAE - Lalmohan, R S (Indian Journal of Fisheries, 2011)
Thirty species of sciaenid fishes so far known from India are classified under 14genera based on the structure of air bladder, otolith and sensory pores. A synoptic keyto the subfamilies and genera is given.